Microbial regulation of arsenopyrite oxidation and arsenic transformation in pyrrhotite-mediated interactions - Shuang Zhou; Yusi Qin; Zhiqi Chen; Zhenlei Cai; Yongjie Bu; Weijian Yu; Chenyang Zhang; Keyi Yang; Min Gan; Qingjun Guan (Bioresource Technology, 2027)

Diisodecyl phthalate aggravates thyroid autoimmune injury in thyroglobulin-sensitized rats via endoplasmic reticulum stress-mediated apoptosis and Th17/Treg dysregulation - Zixin Tian; Jianwei Gao; Zhenjie Lu; Keyi Chen; Wanjia Lv; Mei Ye; Yajun Wang; Yanling Sun; Xu Yang; Ping Ma; Yang Wu (Food and Chemical Toxicology, 2026)

Surface-confined AlOxFy on thermal shock-generated α-Al2O3 for coke-resistant dehydrofluorination of 1,1-difluoroethane - Zhenxiang Li; Yongchao Zhao; Fengqing Hu; Zaizhe Cheng; Keyi Mu; Yuchen Chen; Aimin Chen; Zongjian Liu; Ying Li; Wujian Zhang; Haodong Tang (Chemical Engineering Journal, 2026)

Wind amplification induced by high-rise buildings and identification of local wind-prone neighborhoods using a CFD-machine learning framework - Keyi Chen; Ziwei Mo (Sustainable Cities and Society, 2026)

Assessing the equity and efficiency of crop and livestock-related agricultural greenhouse gas emissions contributes to achieving regionally differentiated emission mitigation - Xin Chen; Yuping Bai; Yecui Hu; Xin Xuan; Gaurav Sikka; Keyi Lyu; Guofeng Wang (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Integrating machine learning with Raman spectroscopy for microplastic identification and classification: Method construction and application - Kaibo Jin; Yanyan Dou; Yang Li; Jingjing Lv; Xuejun Duan; Xudong Chen; Xishu Liang; Tianyu Ao; Keyi Lu; Shoukai Chen (Journal of Water Process Engineering, 2026)

Rapid biodegradation of glyphosate by plant growth-promoting Ochrobactrum sp. Y3: Degradation kinetics, metabolic pathways and environmental bioremediation - Shichen Dai; Chenxi Yan; Mingqiu Liu; Yuxi Sun; Keyi Wang; Guiling Si; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Chemical Engineering, 2026)

Fungal drivers of mycotoxin contamination in wheat: Early warning and plasma-based control - Keyi Zou; Shujuan Chen; Lin Ji; Guoyan Wu; Ke Zhao; Jingxia Fu; Xiumei Yu; Xiaoxue Shan; Likou Zou (Food Research International, 2026)

The acid polysaccharides extracted from Moringa leaf improve DSS-induced ulcerative colitis by targeting intestinal microbiota metabolism - Wen Lang; Xinyun Qin; Yizhe Dou; Keyi Nong; Ruixue Cao; Tingyu Chen; Wanyan Chen; Bin Zhang; Zheng Yang; Bowen Tian; Jijun Wang; Lianbin Li; et al. (Food Research International, 2026)

Machine learning-driven investigation of key flavor factors in pale lager beer fermentation samples and their evolution mechanisms during fermentation - Jiang Xie; Ruiyang Yin; Xin Yuan; Bofeng Zhong; Liyun Guo; Yumei Song; Wenjing Tian; Yiyu Chen; Keyi Ling; Dongrui Zhao; Baoguo Sun; Jinyuan Sun; et al. (Food Chemistry, 2026)

Surface-reconstructed manganese oxides for enhanced external-oxidant-free degradation of bisphenol A: A direct electron transfer mechanism - Dawei Wang; Yihan Zhu; Keyi Gao; Zhuang Liu; Tong Li; Lin Chen; Yilan Jiang (Chemical Engineering Journal, 2026)

Pre-existing liver dysfunction modulates di-(2-ethylhexyl) phthalate (DEHP)-associated biological responses through host-microbiome networks - Mingzhu Wu; Shucong Chen; Wencheng Guo; Sijia Gu; Keyi Li; Yumeng Shi; Yu Qian; Yulian Sun; Yarui Liu; Hongkai Zhu (Environmental Pollution, 2026)

Investigation on Patulin biotransformation in Zebrafish and its toxicological function evaluation - Shuang Li; Shubing Chen; Keyi Fang; Peng Zhu; Sijia Zhang; Shun Zhang; Ting Cai (Mycotoxin Research, 2026)

Lapatinib Induces Ferroptosis in Cardiomyocytes by Regulating ATF4/GPX4 - Yue Sun; Keyi Jiang; Dan Wang; Chunlei Li; Yuqing You; Long Chen; Wei Chang; Liwei Zhang; Hongqi Feng; Dandan Li; Yilan Li (Cardiovascular Toxicology, 2026)

Genetic Variants in EMT-Related lncRNAs Modulate the Risk of Colorectal Cancer in the Chinese Population - Simeng Gu; Zhaohui Zhang; Keyi Cheng; Aibuta Yeerken; Sangni Qian; Fanjia Guo; Mingjuan Jin; Kun Chen (Biochemical Genetics, 2026)

Impact of emission inventory uncertainty on secondary inorganic aerosol simulation over Beijing–Tianjin–Hebei region - Yulong Li; Xiao Tang; Keyi Chen; Lei Kong; Wei Feng; Tianming Lu; Kai Cao; Quan Zhang; Zifa Wang (Atmospheric Pollution Research, 2026)

Post-transcriptional regulation of ABCB1 by miR-34-5p is associated with emamectin benzoate susceptibility in Spodoptera frugiperda - Congsai Wang; Jingdong Li; Zikun Wang; Liying Wu; Huiling Huang; Yunkun Zi; Binrui Bai; Keyi Chen; Hongsong Chen; Huihua Tan; Yutao Xiao; Kaikai Mao (Pesticide Biochemistry and Physiology, 2026)

Root hair-mediated rhizosphere assembly acts as a resilience trait against microplastic-induced dissemination of antibiotic resistance - Zhihui Jin; Guangjun Wang; Yifei Wang; Qing Zhu; Ping Gong; Keyi Chen; Ming Yuan; Huaiying Yao (Journal of Environmental Sciences, 2026)

Self-assembled and reversibly esterified hierarchical networks enable tough, anti-swelling and recyclable nanocomposite hydrogel - Zhengxu Jin; Ying Chen; Feihong Hu; Huizhu Wang; Qianyue Zeng; Keyi Yang; Hong Chen; Xiaoming Huang; Jing Xie; Jianshu Li (Chemical Engineering Journal, 2026)

Improving the Spatiotemporal Forecasting of PM2.5 by Coupling a Deep Learning Method with a Chemical Transport Model: A Severe Haze Case in China - Zheng Zhao; Huangjian Wu; Keyi Chen; Lei Kong; Xiao Tang (Aerosol Science and Engineering, 2026)

Corrigendum to ‘Constitutive overexpression of ATP-binding cassette transporters contributes to emamectin benzoate resistance in Spodoptera frugiperda’ [Pesticide Biochemistry and Physiology, 219 (2026) 106980] - Congsai Wang; Zikun Wang; Jingdong Li; Yunkun Zi; Huiling Huang; Binrui Bai; Keyi Chen; Jing Wang; Hongsong Chen; Huihua Tan; Kaikai Mao (Pesticide Biochemistry and Physiology, 2026)

Ruthenium supported on grain-boundary-induced oxygen-vacancy-rich CeO2 for efficient ammonia decomposition - Jinghua Liu; Wujian Zhang; Junhan Yang; Yongchao Zhao; Jian Guan; Zhenxiang Li; Keyi Mu; Yuchen Chen; Aimin Chen; Zongjian Liu; Chunshan Lu; Angjian Wu; et al. (Chemical Engineering Journal, 2026)

Constitutive overexpression of ATP-binding cassette transporters contributes to emamectin benzoate resistance in Spodoptera frugiperda - Congsai Wang; Zikun Wang; Jingdong Li; Yunkun Zi; Huiling Huang; Binrui Bai; Keyi Chen; Jing Wang; Hongsong Chen; Huihua Tan; Kaikai Mao (Pesticide Biochemistry and Physiology, 2026)

Generation of environmentally persistent free radicals in paddy soil and their impact on arsenic speciation and bioavailability: A review - Chen Chen; Nan Yang; Xiaotong Liu; Yi Zhou; Keyi Wang; Naiyi Yin; Xiaolin Cai; Yanshan Cui (Journal of Hazardous Materials, 2026)

Enhanced Chaetoceros muelleri growth using optimized fermented agricultural waste - Yong Feng; Keyi Li; Yutong Xia; Ping Wu; Zhen Wang; Shuhao Huo; Guoqiang Guan; Huayou Chen (Systems Microbiology and Biomanufacturing, 2026)

Dual-modal antioxidant nanozyme hydrogel for protection against noise-induced hearing loss via attenuation of oxidative stress and NF-κB/MAPK signaling - Liang Xia; Ru Tang; Yi Chen; Ning Ma; Lili Xiao; Xiaoyan Chen; Xiaoyin Mao; Keyi Li; Yanmei Feng; Jingjing Liu; Amin Zhang (Chemical Engineering Journal, 2026)

β-Ionone inhibits A. sydowii mediated LUAD progression by inhibiting myeloid-derived suppressor cell (MDSC) expansion and activation - Xiaoping Liu; Shuhua Li; Keyi Chen; Xue Yang; Yanxia Yang; Xin Wang (Journal of Molecular Histology, 2026)

UVB enhances SLC6A15-mediated phenylalanine transport to promote melanogenesis - Shu Zhou; Yujie Ouyang; Yibo Hu; Xixia Dai; Ling Jiang; Chuhan Fu; Yaqing Wen; Jiangfeng Huang; Keyi Zhang; Jing Chen; Qinghai Zeng (Journal of Photochemistry and Photobiology B: Biology, 2026)

Rapid nucleation and wall-climbing growth of methane hydrate by expanded graphite laminates under static high water-loading conditions - Huizhen Yu; Zixuan Song; Keyi Zhong; Daoyi Chen; Yuanyin Wang; Zihan Yue; Jun Duan; Shuyi Jiang; Mucong Zi (Chemical Engineering Journal, 2026)

Discovery and Optimisation of Novel Bombinin-Derived Peptides from Bombina variegata against Staphylococcus aureus - Jiachen Liu; Keyi Yao; Ruize Sun; Xiaonan Ma; Chengbang Ma; Xiaoling Chen; Yangyang Jiang; Tao Wang; Tianbao Chen; Chris Shaw; Mei Zhou; Lei Wang (Probiotics and Antimicrobial Proteins, 2026)
Amphibian skin-secreted antimicrobial peptides (AMPs) have garnered significant attention for their excellent biological activity and low propensity for drug resistance over the past 40 years. Bombinins and bombinin H, two classes of AMPs isolated from the skin secretions of Bombina species, demonstrate strong antimicrobial activity against broad-spectrum microorganisms. In this study, two novel peptides, bombinin-like peptide 7S and bombinin-H2L, were identified from the toad, Bombina variegata . While both peptides exhibited broad-spectrum antimicrobial activity, they also showed relatively high cytotoxicity. To explore the structure–activity relationship and enhance therapeutic potential, bombinin-H2L, which displayed stronger average antimicrobial activity, was used as a template. With the aid of bioinformatics analysis, a series of bombinin-H2L analogues were designed by increasing the net positive charges and/or adjusting the amphiphilicity of the parent peptide. Among these analogues, [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L demonstrated high therapeutic efficacy and specificity toward clinically isolated, drug-resistant Staphylococcus aureus strains in both in vitro and ex vivo tests. Their notable biosafety profiles, sensitivity to diverse environments, and ability to disrupt biofilms highlight their potential for further development. Additionally, studies on the mechanism of [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L revealed a membrane-targeted antimicrobial mechanism, with its antibacterial function exerted by disrupting the integrity of bacterial membranes. These findings provide valuable insights into structural modifications of bombinin H peptides for enhanced activity, and [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L have the potential as promising candidates for novel antibacterial agents in treated bacterial skin infections.

Enhanced buoy-based water quality time series imputation in coastal waters - Minyu Wang; Keyi Yang; Junyu He; Jin Qi; Yijun Chen; Haoqi Gu; Renyi Liu; Sensen Wu; Zhenhong Du (Journal of Hydrology, 2025)

A high-performance aqueous redox flow battery with long cyclic stability enabled by a novel Janus membrane self-assembled from polyelectrolytes - Quanhu Sun; Keyi Dong; Zefeng Yan; Tian Lv; Yan Tan; Jiaxin Yang; Yu Wang; Weiyang Tang; Tao Chen (Chemical Engineering Journal, 2025)

Emergence and genomic characterization of Vibrio parahaemolyticus serotype O10:K4 from seafood-linked diarrheal cases in Zhejiang, China (2016–2023) - Jiewen Huang; Zhen Zhang; Qingtian Li; Jiancai Chen; Lingling Mei; Xiaojuan Qi; Lili Chen; Junyan Zhang; Chao Lv; Min Li; Honghu Chen; Yanjun Zhang; et al. (Food Research International, 2025)

Selective enrichment of comammox over NOB Nitrospira on biofilm in low-oxygen integrated fixed-film activated sludge system - Yunlong Li; Jin Chen; Bowen Wang; Naif Abdullah Al-Dhabi; Zimin Chai; Keyi Zhang; Shujun Huang; Wangwang Tang; Maosheng Zheng (Journal of Environmental Chemical Engineering, 2025)

Imidazolium salt-functionalized Cu2O@SiO2 catalysts for integrated CO2 capture and electroreduction to multi-carbon products in acidic electrolytes - Hui Zhang; Shanshan Lou; Fan Yang; Keyi Fan; Zhengxin Gu; Wangbo Li; Yihe Chen; Yizhen Gan; Lushan Ma; Guoliang Wang; Hui Yang (Chemical Engineering Journal, 2025)

MicroalgaeNet: Enhancing recognition of long-tailed marine microalgae images through multi-expert networks and feature compression - Keyi Chen; Sijing Cui; Jiajun Zhong; Qiwei Wang (Algal Research, 2025)

The spatial-temporal pattern of RMT network stability in the estuarine phytoplankton community - Mingliang Zhou; Yan Xu; Keyi Zhu; Tong Teng; Xumeng Huo; Xinyue Chen; Weili Hou; Jiaqiang Liu; Shengjun Yan; Imran Khan (Journal of Environmental Management, 2025)

Insights into metal site effects on adsorption-hydration methane storage in water-based MOF system - Jun Duan; Jie Li; Keyi Zhong; Hongyu Ye; Yuanxin Yao; Daoyi Chen; Shujun Chen; Mucong Zi (Chemical Engineering Journal, 2025)

Impacts of biodegradable microplastics on rhizosphere bacterial communities of Arabidopsis thaliana: Insights into root hair-dependent colonization - Keyi Chen; Zhihui Jin; Qing Zhu; Xiaodie Hu; Sijia Tian; Yulin Wang; Yaru Sun; Ming Yuan; Huaiying Yao (Environmental Research, 2025)

Synergizing farmland reverting and energy substitution programs in Wolong through agent-based modelling and cost-efficiency analysis - Keyi Liu; Yufeng Chen; Liyan Xu; Xiao Zhang; Zilin Wang; Hailong Li; Yansheng Yang; Hong You; Dihua Li (Ecological Modelling, 2025)

Chromosomal structural variation loci HSS1 and HSS6 lead to hybrid sterility in rice - Siqi Cheng; Zhenwei Xie; Hao Yu; Chaolong Wang; Xiaowen Yu; Jian Wang; Hai Zheng; Jiayu Lu; Xiaodong He; Keyi Chen; Junwen Gao; Yang Hu; et al. (Theoretical and Applied Genetics, 2025)

Non-degradable microplastic promote microbial colonization: A meta-analysis comparing the effects of microplastic properties and environmental factors - Zhihui Jin; Keyi Chen; Qing Zhu; Xiaodie Hu; Sijia Tian; Airong Xiang; Yaru Sun; Ming Yuan; Huaiying Yao (Environmental Research, 2025)

Geochemical behaviors of metal elements during a single flood event in the natural Chishui River, Southwest China - Zhongxuan Liang; Keyi Wang; Hongming Cai; Zhongwei Wang; Wei Yuan; Jiubin Chen (Acta Geochimica, 2025)

Microscopic influence mechanisms of pre-adsorbed polysaccharide on the nucleation and growth of methane hydrate on metal surface - Ruihua Luo; Keyi Zhong; Daoyi Chen; Guozhong Wu; Li Wang; Mucong Zi (Fuel, 2025)

Insight into the micro-mechanism of hydrate-based methane storage from active ice - Jun Duan; Keyi Zhong; Shuyi Jiang; Daoyi Chen; Guangjin Chen; Mucong Zi (Fuel, 2025)

Reconstruction of cobalt atoms in ZIF-67 and in-situ growth of carbon nanotubes at low temperature for High-Performance strain sensors - Xiao Li; Tian Lv; Keyi Dong; Jiaxin Yang; Weiyang Tang; Zilin Chen; Yu Duan; Quanhu Sun; Dongmei Zhai; Tao Chen (Chemical Engineering Journal, 2025)

OsPAD1, encoding a non-specific lipid transfer protein, is required for rice pollen aperture formation - Qiming Wang; Yunlu Tian; Keyi Chen; Shanshan Zhu; Yehui Xiong; Chaolong Wang; Xiaowen Yu; Wenting Bai; Hai Zheng; Shimin You; Yang Hu; Dekun Lei; et al. (Plant Molecular Biology, 2025)

Inoculation of thermophilic bacteria from giant panda feces into cattle manure reduces gas emissions and decreases resistance gene prevalence in short-term composting - Jingxia Fu; Shujuan Chen; Yulan Tan; Keyi Zou; Xiumei Yu; Lin Ji; Jianmin Zhang; Xingning Xiao; Wen Wang; Ke Zhao; Likou Zou (Journal of Environmental Management, 2025)

Preparation, separation, and identification of antioxidant peptides from protein hydrolysate of Polygonatum cyrtonema Hua - Yanyan Zhang; Shengjun Ma; Haixia Li; Peizi Liu; Keyi Chen; Wei Cai (Food Bioscience, 2024)

A microphase-separation ionogel electrolyte for highly stretchable all-solid-state supercapacitors - Weiyang Tang; Keyi Dong; Zilin Chen; Yu Duan; Quanhu Sun; Xiao Li; Dongmei Zhai; Tian Lv; Tao Chen (Chemical Engineering Journal, 2024)

Metal plate-based promotion on methane hydrate nucleation: Insights into the influence of metal type and surface properties - Yuanyin Wang; Mucong Zi; Shuyi Jiang; Keyi Zhong; Daoyi Chen (Chemical Engineering Journal, 2024)

Regulating the generation of singlet oxygen (1O2) in Advanced oxidation processes by catalyst design for water treatment - Yilan Jiang; Keyi Gao; Tingyue Chen; Yiran Xiong; Yingying Li; Abrham Addisu; Suresh C. Pillai; Dionysios D. Dionysiou; Dawei Wang (Chemical Engineering Journal, 2024)

Separation cathode materials from current collectors of spent lithium-ion battery through low-energy mechanical friction technology - Keyi Lin; Yusen Wu; Ying Shen; Yanrui Zheng; Zicheng Wang; Jinjuan Chen; Taoli Wu; Jie Zhu; Zhe Huang; Baojia Qin; Jujun Ruan (Resources, Conservation and Recycling, 2024)

6:2 Cl-PFESA, a proposed safe alternative for PFOS, diminishes the gemcitabine effectiveness in the treatment of pancreatic cancer - Jiawei Hong; Keyi Du; Weichen Zhang; Junran Chen; Hangbiao Jin; Yuanchen Chen; Yifan Jiang; Hanxi Yu; Xiaoyu Weng; Shusen Zheng; Jun Yu; Linping Cao (Journal of Hazardous Materials, 2024)

Rational design of bilayer heterogeneous poly(ionic liquid)s electrolytes for high-performance flexible supercapacitors with ultraslow self-discharge rate - Keyi Dong; Weiyang Tang; Quanhu Sun; Zilin Chen; Xiao Li; Dongmei Zhai; Zefeng Yan; Jiaxin Yang; Tian Lv; Tao Chen (Chemical Engineering Journal, 2024)

Hyperaccumulator extracts promoting the phytoremediation of rare earth elements (REEs) by Phytolacca americana: Role of active microbial community in rhizosphere hotspots - Shengpeng Yan; Shengwen Xu; Shihan Lei; Yuan Gao; Keyi Chen; Xiaoyu Shi; Yingying Guo; Nataliya Bilyera; Ming Yuan; Huaiying Yao (Environmental Research, 2024)

High nutrient utilization and resorption efficiency promote bamboo expansion and invasion - Keyi Zuo; Lili Fan; Ziwu Guo; Le Zhang; Yiyang Duan; Jingrun Zhang; Shuanglin Chen; Hua Lin; Ruicai Hu (Journal of Environmental Management, 2024)

Biomineralization-inspired porous calcium carbonate microspheres as a controlled release system of herbicides/pesticides - Yaoxun Zeng; Xinyi Li; Fangzheng Chen; Huiling Ye; Keyi Rong; Zhili Ran; Binhong Liu; Zhenxing Pan; Xiuxian Xie; Junze Tang; Xujie Liu; Yan He (Journal of Environmental Chemical Engineering, 2024)

Core-shell nanoconfinement: Nanoreactors for directional electron migration in photothermal-assisted photocatalytic hydrogen production - Yu Shen; Yuxing Shi; Zhouze Chen; Shunhong Zhang; Keyi Chen; Xuefeng Luo; Feng Guo; Guangzhao Wang; Weilong Shi (Chemical Engineering Journal, 2024)

Degradation mechanism analysis of substrate and microporous layer of gas diffusion layer in proton exchange membrane fuel cell - Keyi Xu; Qian Di; Fengman Sun; Ming Chen; Haijaing Wang (Fuel, 2024)

Environment relevant exposure of perfluorooctanoic acid accelerates the growth of hepatocellular carcinoma cells through mammalian target of rapamycin (mTOR) signal pathway - Jiawei Hong; Xiaoyan Wang; Hangbiao Jin; Yuanchen Chen; Yifan Jiang; Keyi Du; Diyu Chen; Shusen Zheng; Linping Cao (Environmental Pollution, 2024)

A gradient structured SEI enabling record-high areal capacity anode for high-rate Mg metal batteries - Ming Hu; Guyue Li; Keyi Chen; Xuejun Zhou; Chilin Li (Chemical Engineering Journal, 2024)

Constructing bilayer heterogeneous organogel electrolytes of Lewis acidic/basic polymers to suppress self-discharge of supercapacitors - Yanan Liu; Keyi Dong; Tian Lv; Zilin Chen; Shaokui Cao; Feng Zheng; Tao Chen (Chemical Engineering Journal, 2024)

The flexible linker and CotG were more effective for the spore surface display of keratinase KERQ7 - Zhen Wang; Mingchen Yan; Muhammad Saeed; Keyi Li; Yanzhen Chen; Charles Obinwanne Okoye; Zhen Fang; Zhong Ni; Huayou Chen (World Journal of Microbiology and Biotechnology, 2024)

The translocation and fractionation of rare earth elements (REEs) via the phloem in Phytolacca americana L. - Yingying Guo; Shengwen Xu; Shengpeng Yan; Shihan Lei; Yuan Gao; Keyi Chen; Xiaoyu Shi; Ming Yuan; Huaiying Yao (Environmental Science and Pollution Research, 2023)

A novel hydrogel electrolyte for all-climate high-performance flexible zinc-ion hybrid capacitors within temperature range from −50 to 100 °C - Yu Duan; Tian Lv; Keyi Dong; Feng Zheng; Xiao Li; Yunlong Qi; Zilin Chen; Weiyang Tang; Quanhu Sun; Shaokui Cao; Tao Chen (Chemical Engineering Journal, 2023)

Improving quantification of methane point source emissions from imaging spectroscopy - Zhipeng Pei; Ge Han; Huiqin Mao; Cuihong Chen; Tianqi Shi; Keyi Yang; Xin Ma; Wei Gong (Remote Sensing of Environment, 2023)

Progress in the cultivation of diatoms using organic carbon sources - Keyi Li; Yutong Xia; Zhen Wang; Ebin Gao; Shuhao Huo; Huayou Chen (Algal Research, 2023)

Effect of combined ultrasonic and enzymatic assisted treatment on the fermentation process of whole Lycium barbarum (goji berry) fruit - Yunfeng Hu; Keyi Li; Yahui Bai; Haichuan Li; Junran Chen (Food Bioscience, 2023)

Physical activity can influence the relationship between ethylene oxide and risk of kidney stones: A cross-sectional study from the NHANES 2013–2016 - Hua Jiang; Keyi Wang; Heng Zhang; Bin Yang; Weipu Mao; Ming Chen; Shuigen Zhou (Environmental Science and Pollution Research, 2023)

Microplastic pollution destabilized the osmoregulatory metabolism but did not affect intestinal microbial biodiversity of earthworms in soil - Ronggui Tang; Minshen Ying; Yongming Luo; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Tao Sun; Yutao Cao; Zhihan Diao; Yuxin Zhang; Yichen Lian; Keyi Chen; Yan Yan; et al. (Environmental Pollution, 2023)

Kynurenic acid mediates bacteria-algae consortium in resisting environmental cadmium toxicity - Xiaoli Qi; Keyi Fu; Mingyuan Yue; Na Shou; Xuefeng Yuan; Xi Chen; Chunyu He; Yunfeng Yang; Zunji Shi (Journal of Hazardous Materials, 2023)

Construction of core–shell FeS2@ZnIn2S4 hollow hierarchical structure S-scheme heterojunction for boosted photothermal-assisted photocatalytic H2 production - Keyi Chen; Yuxing Shi; Ping Shu; Zhenyu Luo; Weilong Shi; Feng Guo (Chemical Engineering Journal, 2023)

Nanoplastics induce molecular toxicity in earthworm: Integrated multi-omics, morphological, and intestinal microorganism analyses - Ronggui Tang; Dong Zhu; Yongming Luo; Defu He; Haibo Zhang; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Keyi Chen; Yan Yan; Xinghang Lu; Minshen Ying; Tao Sun; et al. (Journal of Hazardous Materials, 2023)

Modulation of Spike Count Correlations Between Macaque Primary Visual Cortex Neurons by Difficulty of Attentional Task - Qiyi Hu; Wenjuan Hu; Keyi Liu; Xiangdong Bu; Lisha Hu; Liming Li; Xinyu Chai; Yao Chen (Neuroscience Bulletin, 2022)

Cloning and expression analysis of juvenile hormone epoxide hydrolase-like ( EsJHEH-like ) from Eriocheir sinensis , and its potential roles in methyl farnesoate metabolism - Tiantian Chen; Yingzhu Diao; Ruihan Xu; Na Sheng; Fan Liu; Qiming Xie; Shiping Su; Keyi Ma; Xilei Li (Invertebrate Reproduction & Development, 2022)

Effect of Dissipation on the Moonpool-Javelin Wave Energy Converter - Dan Yu; Keyi Wang; Yeqing Jin; Fankai Kong; Hailong Chen; Can Yang (Journal of Marine Science and Engineering, 2021)
In this work, the hydrodynamic performance of a novel wave energy converter (WEC) configuration which combines a moonpool platform and a javelin floating buoy, called the moonpool–javelin wave energy converter (MJWEC), was studied by semianalytical, computational fluid dynamics (CFD), and experimental methods. The viscous term is added to the potential flow solver to obtain the hydrodynamic coefficients. The wave force, the added mass, the radiation damping, the wave capture, and the energy efficiency of the configuration were assessed, in the frequency and time domains, by a semianalytical method. The CFD method results and the semianalytical results were compared for the time domain by introducing nonlinear power take-off (PTO) damping; additionally, the viscous dissipation coefficients under potential flow could be confirmed. Finally, a 1:10 scale model was physically tested to validate the numerical model and further prove the feasibility of the proposed system.

Evaluation of All-Sky Assimilation of FY-3C/MWHS-2 on Mei-yu Precipitation Forecasts over the Yangtze-Huaihe River Basin - Yu Li; Keyi Chen; Zhipeng Xian (Advances in Atmospheric Sciences, 2021)

Growing Operational Use of FY-3 Data in the ECMWF System - Niels Bormann; David Duncan; Stephen English; Sean Healy; Katrin Lonitz; Keyi Chen; Heather Lawrence; Qifeng Lu (Advances in Atmospheric Sciences, 2021)

Changes of soil organic matter stability along altitudinal gradients in Tibetan alpine grassland - Yanhui Hou; Keyi He; Ying Chen; Jingxue Zhao; Huifeng Hu; Biao Zhu (Plant and Soil, 2021)

Carboniferous integrative stratigraphy and timescale of China - Xiangdong Wang; Keyi Hu; Wenkun Qie; Qingyi Sheng; Bo Chen; Wei Lin; Le Yao; Qiulai Wang; Yuping Qi; Jitao Chen; Zhuoting Liao; Junjun Song (Science China Earth Sciences, 2019)

Assimilation of Feng-Yun-3B satellite microwave humidity sounder data over land - Keyi Chen; Niels Bormann; Stephen English; Jiang Zhu (Advances in Atmospheric Sciences, 2018)

Dihydromyricetin Ameliorates 3NP-induced Behavioral Deficits and Striatal Injury in Rats - Shuhua Mu; Youlan Li; Bingbing Liu; Weiping Wang; Si Chen; Jiajia Wu; Lisi OuYang; Yaxi Zhu; Keyi Li; Mali Zhan; Zongwei Liu; Yu Jia; et al. (Journal of Molecular Neuroscience, 2016)

A novel SNP of the Hesx1 gene in bovine and its associations with average daily gain - Xinsheng Lai; Xianyong Lan; Hong Chen; Xinlei Wang; Keyi Wang; Mou Wang; Hui Yu; Miao Zhao (Molecular Biology Reports, 2009)